The Enchanted Castle - Nesbit, E (Wordsworth Editions Ltd, 1998)
During their vacation from school, English siblings Gerald, Jimmy, and Kathleen, with their friend, Mabel, discover an enchanted ring that makes wishes come true, but with unexpected consequences.
Keywords: Fantasy; Fiction; General